Teachers' perceptions toward transformational leadership and its relation to trust among their principals - Abu-Tineh, Abdullah; Khasawneh, Samer (Jordan Journal of Educational Sciences, 2006)
The aim of this study was to investigate the impact of transformational leadership of school principals along with their demographic variables on teachers' trust. Moreover, the relationship between the six dimensions of transformational leadership and trust was studied. Results showed strong, positive, and significant relationship between transformational leadership overall and trust dimension. Furthermore, the relationship between each dimension of transformational leadership and trust was found to be moderate, positive, and significant. However, the effect of demographic variables was insignificant. Finally, theoretical and practical suggestions were provided.